Detection and Differentiation of Liquid and Solid Particles in Ambient Air. Issue 10 (8th September 2021) - Westphal, Danny; Teumer, Tobias; Schäfer, Thomas; Ahlers, Rolf‐Jürgen; Rädle, Matthias
Abstract: Aerosols contain liquid and/or solid particles, which can pose a significant risk to humans. In order to detect these potential hazards at an early stage, this paper shows the possibility of measuring aerosols with an adapted particle sensor system (ProxiCube®) and displaying the liquid and solid components separately. To demonstrate the reproducibility of the measurements, samples are monitored simultaneously with two ProxiCubes and a well‐established reference system. Abstract : Aerosols can be present in the air in liquid and/or solid form. These particles can pose a significant risk to humans. In order to detect these potential hazards at an early stage, the possibility of reliably measuring aerosols with an adapted particle sensor system is demonstrated.